THE ECONOMY OF UZBEKISTAN AND THE ROLE OF THE DEVELOPMENT OF THE SERVICE SECTOR - Ibrahimov, Shertoy (Science technology&Digital finance, 2023)
Annotation. The article analyzes the concept of the service sector as an economic category. The role of the service sector in the economy of the countries of the world and Uzbekistan is analyzed. Trends in the development of the service sector in 2017-2022 have been fully studied by the main types. The dynamics of enterprises and organizations working in this field in recent years has been analyzed. Prospects for further development of the service sector are highlighted.